Effectiveness of Mediation in Divorce Settlement in Klaten Religious Court - Mahendra Jaya Gumilang (Proceeding International Conference Restructuring and Transforming Law, 2025)
The divorce rate in Indonesia shows an increasing trend in recent years. In particular, in Klaten Regency, the divorce rate has also increased significantly. The increase in the divorce rate is a serious concern for the government and society, considering its impact on the social structure and family welfare. In divorce cases, mediation is often a means of identifying the root of problems in the household, such as communication conflicts, economic problems, or third party intervention. Thus, this research aims to find out how effective mediation is in resolving divorce cases at Klaten Religious Court and what factors influence the success or failure of mediation in divorce cases. This research uses a juridical-sociological approach to understand the effectiveness of mediation in resolving divorce cases, both from a legal perspective and its social implementation related to divorce resolution. The mediation process carried out by Klaten Religious Court has been deemed effective. The results of research on the effectiveness of the mediation process in resolving divorce at Klaten Religious Court, quantitatively, the mediation process carried out by Klaten Religious Court has shown success in many divorce cases. The main factor that supports the success of mediation is the competence of the mediator involved in the process, which includes skills in managing conflict dynamics and building effective communication between the disputing parties. Apart from that, the willingness to reconcile from the parties involved in the case also greatly influences the success of mediation. Even though the mediation system at Klaten Religious Court has had a positive impact, improvements are still needed, both in terms of the quality of mediators, active participation of litigants, and support from court institutions to overcome existing obstacles.